Urban Atmospheric Aerosols (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The challenges faced by the atmospheric research community today are vast, complex, and multi-faceted. The book Urban Atmospheric Aerosols: Sources, Analysis, and Effects highlights important aspects concerning the chemical and optical properties, size distribution, sources, and potential health effects of fine urban air particles (PM2.5). The physical and chemical characterization of PM2.5, its source assignment, and the assessment of the magnitude and distribution of its emissions are crucial for establishing effective fine air particle regulations and assessing the associated risks to human health. This book brings together eight papers covering the main topics of the field and will be of interest to researchers who are interested in air quality in outdoor and indoor environments, air particle toxicity, and atmospheric chemistry, as well as global climate modelers.